Grafomotor test validation in normal school children in Lima-Peru - Bojórquez, María (2005)
Objective: To obtain a quick and reliable grafomotor maturation test during an office consultation. Materials and Methods: We studied the validity and reliability of the grafomotor test (TGM – Copying 8 figures in 10 minutes) in a middle class school children population. Another needy settlement population was chosen to value the socioeconomic level influence on the results. Statistical analysis consisted in Pearson correlations for two quantitative variables and multiple step lineal regression for various quantitative variables. Reliability was calculated by Cronbach’s alpha coefficient. Results: The TGM showed its validity because it confirmed scores improve with increasing age. Age or school grade correlation punctuations were above 0,8. The reliability test retest for age group did not reach significant statistical difference. The alpha Cronbach coefficient was 0,9. Reliability among different correctors was also good. Average difference between the two populations was fundamentally due to age. Conclusions: The TGM applied to normal school children obtained good test retest and interobserver reliability, as well as high validity compared to the original study and to Bender’s test. It can be used as a screening test during the office consultation in order to decide which patient needs a complete neuropsychological evaluation.